Paradigma Pembelajaran dan Motivasi Belajar Siswa - Miftahussaadah Miftahussaadah; Subiyantoro Subiyantoro (ISLAMIKA, 2021)
Learning is a conscious effort to achieve a learning goal. In the latest educational paradigm, the purpose of learning is no longer just to change the behavior of students, but rather to form a professional character and psychological attitudes in all aspects. To achieve this goal requires a motivation. Motivation to learn contained in a person has a very important role in achieving a goal, because motivation can make someone have a strong urge to do something. In this case, the teacher has a significant role in fostering student motivation to achieve learning goals and the needs of the changing times as well as demands for a change in the learning paradigm. Therefore, this article aims to understand the meaning of the learning paradigm and the importance of fostering student motivation in learning activities.